2017
DOI: 10.1080/09513590.2017.1334200
|View full text |Cite
|
Sign up to set email alerts
|

Neurovegetative disorders of perimenopausal women treated with docosahexaenoic acid (DHA, 625 mg)

Abstract: The study evaluated the effect of DHA 625 mg in women who experience menopausal symptoms, on sexuality and quality of life (QoL), and on the auditory brainstem response (ABR). Forty-two perimenopausal women were enrolled. The Kupperman Index (KI) was used to evaluate menopause symptoms. The Short Form-36 (SF-36), Female Sexual Function Index (FSFI), and the Female Sexual Distress Scale (FSDS) were used to assess QoL, sexual function, and sexual distress, respectively. Auditory evoked potentials to measure the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For example, docosahexaenoic acid (DHA, 625 mg) can be effective in modulating some perimenopausal symptoms in women and consequently can contribute to improve their quality of life. It seems to have a direct activity on the neuronal conduction time into the audiological system [16]. Another study done in this regard was conducted to determine the effects of the monophasic oral contraceptive containing 30 mcg ethinylestradiol and 3 mg drospirenone on the nasal respiratory epithelium in premenopausal women, which showed that maturation index of the nasal respiratory epithelium seems to depend on the variation of the ovarian steroids during the menstrual cycle and on the iatrogenic effects of oral contraception [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, docosahexaenoic acid (DHA, 625 mg) can be effective in modulating some perimenopausal symptoms in women and consequently can contribute to improve their quality of life. It seems to have a direct activity on the neuronal conduction time into the audiological system [16]. Another study done in this regard was conducted to determine the effects of the monophasic oral contraceptive containing 30 mcg ethinylestradiol and 3 mg drospirenone on the nasal respiratory epithelium in premenopausal women, which showed that maturation index of the nasal respiratory epithelium seems to depend on the variation of the ovarian steroids during the menstrual cycle and on the iatrogenic effects of oral contraception [17].…”
Section: Discussionmentioning
confidence: 99%